Pengaruh Kompetensi Pegawai Terhadap Kepuasan Penyedia Pengadaan Barang Dan Jasa Dalam Menggunakan Aplikasi E-Procurement Di Pemerintah Daerah Kota Cimahi - Eka Susilawati; Yudi Darsono; Aditia Mulawarman (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
Based on the results of research conducted by researchers at the Cimahi City Office, researchers found the problem was the low level of satisfaction of providers of goods and services procurement. The purpose of this study is to determine the extent to which employee competence relates to the satisfaction of goods and services procurement providers in using e-procurement applications in the Cimahi City Regional Government. The method used in this research is a quantitative research method through a descriptive approach. The number of community samples listed is a sample of 62 members of the population. The survey results reveal that there is a correlation between employee competence and satisfaction. The large correlation coefficient is 0.848 (R). R in the correlation, or the correlation between two or more independent variables on the dependent variable shows moderate correlation. The influence of competence on satisfaction is classified as a fairly high influential category of 71.9%, this proves that employee competence has a positive and significant effect on the satisfaction of providers of goods and services, while the remaining 28.1% is the influence of other variables not examined in this study.